2005
DOI: 10.1007/s00018-004-4403-6
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of endogenous bacteriophages in controlling invading pathogens

Abstract: Bacteriophages (phages) are omnipresent in our environment, and recent studies highlight their potential impact on the microbial world. Phages can also be present in mammalian organisms, including man (intestines, oral cavity, urine, sputum and serum). Data are available which suggest that those endogenous phages could play an important role in eliminating bacteria and regulating the body ecosystem. Furthermore, our most recent findings suggest that phages can exert immunosuppressive action in the gut, helping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
93
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(98 citation statements)
references
References 120 publications
4
93
0
1
Order By: Relevance
“…121 It has been shown that there is a threshold density of bacteria which causes mortality in untreated animals that is reduced by treatment with phages. 118 Direct influences of phages on the immune system have also been recently documented.…”
Section: Direct Phage Effects On the Mammalian Host Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…121 It has been shown that there is a threshold density of bacteria which causes mortality in untreated animals that is reduced by treatment with phages. 118 Direct influences of phages on the immune system have also been recently documented.…”
Section: Direct Phage Effects On the Mammalian Host Immune Systemmentioning
confidence: 99%
“…Thus, intestinal phages may not only eliminate harmful bacteria and reduce commensal bacteria but may also modulate local immune reactions directly themselves. 121 Riley 131 hypothesized that as phages are immunogenic, these particles could play a role in the pathogenesis of autoimmune and other inflammatory diseases by acting as antigens on epithelial surfaces, by binding to antibodies as immune complexes, through molecular mimicry or as superantigens. The immunogenic effect could take place when phage particles approach high numbers after lytic infection of the normal flora.…”
Section: Direct Phage Effects On the Mammalian Host Immune Systemmentioning
confidence: 99%
“…They have been isolated from aquatic systems in quantities ranging from 10 4 plaque forming units (PFU) to more than 10 8 PFU/ mL, in fresh water sediments in ranges of 0.65 PFU to 3x10 9 PFU/g, and in marine environments in quantities over 12x10 9 PFU/mL. In soils, concentrations of 0.7 to 2.7x10 8 PFU/g have been found (Gorski and Weber-Dabrowska 2004). Some bacteriophages are highly specific attacking only certain bacterial strains, while others are quite broad in their host range (Skurnik and Strauch 2006).…”
Section: General Characteristics Of Bacteriophagesmentioning
confidence: 99%
“…This phenomenon, which occurs within minutes or hours, shows that the viral particles are autoreplicative entities at least as long as a bacterial population in sufficient numbers to support this event exists. Their lytic mechanism from an ecological viewpoint constitutes a predator/prey system, and from an epidemiological viewpoint a host-parasite model (Gorski and Weber-Dabrowska 2004). The phenomenon of transduction (transfer of bacterial DNA via phage) is rare in lytic phages (Monk et al 2010).…”
Section: General Characteristics Of Bacteriophagesmentioning
confidence: 99%
“…recent decades bacteriophages have been used as treatment agents against some human and animal pathogens such as E.coli and gastrointestinal infections (8)(9)(10). Also, the use of bacteriophage in the plants may protect them via reduction in plant bacterial disorders (11).…”
Section: Soleimani Delfan a Et Al Isolation Of Pseudomonas Putida Bamentioning
confidence: 99%